Privatheit wider Willen? : Verhinderung informationeller Preisgabe im Internet nach deutschem und US-amerikanischem Verfassungsrecht - Sandfuchs, Barbara (Internet und Gesellschaft Ser. ;, 2015)
Competent adult internet users voluntarily disclose vast amounts of personal data. As such disclosure can cause great harm, governments may feel that through minor interventions they can protect their citizens from disclosure that is not in the latters' best interest. However, such actions can infringe upon the rights of the users' and of the data collectors', and are only licit when justified. Neither the German nor the US government has the duty or the power to coerce the privacy choices of competent adult users for the sole purpose of protecting them against dangers caused by themselves. Instead, it is suggested that governments should focus on limiting specific harmful disclosure.